A gestão da demanda na cadeia de suprimentos do setor hoteleiro brasileiro - Moysés, Gerson Luís Russo (2007)
The demand management is an emerging theme in the chain management knowledge field. What is aimed with the demand management is the fast and adequate integration of the needs originated from the market to the suppliers in a way to strategically balance and align the demand with the operacional capacity throught the supply chain and, consequently, the competitive advantage. However, with the market dynamic in which the clients are even more demanding and the commercial exchange regulations are less restrict, the alignment of the demand with the supply chain progressively face progressive difficulties. Because of that, this research had as an objective to verify alignment among the demand management, operational capacity and financial and operational performance variables, in hotel companies of national and international funds, in operation in Brazil. For that, a theoretical model was developed, that considered these variables. The research was achieved in two stages. In the first one, considered exploratory and qualitative, the focus group technic was used to data collection. The data collection was treated by the contend analysis. With the results of this first step a questionnaire was elaborated, which was used in the next stage. In the second stage, through the data collection by means of a structured questionnaire it was intended to characterize the demand management, capacity management and the imediate chain variables in the searched hotels. From the total of sent questionnaires, 121 answers were turned back. The obtained data were treated by the descriptive statistics and by the tests: a) Kolmogorov-Smirnov, to verify the sample normality; b) Spearman s bivariated correlation analysis, in order to verify the alignment among the variables and; c) Mann-Whitney, to find if the variables that pertained to groups of hotels were distinct. The data which was submitted to the statistic treatment showed the following results: 1) when it was used the descriptive statistics, the luxury group hotels presented a higher frequency of answers, in the agreeable side of the scale and superior financial and operational performance if compared to the economic group hotels; 2) when it was used the bivariated correlation, the luxury group hotels showed a higher number of demand management, operational capacity and financial and operational performance variables, correlated, and financial and operational performance which was superior to the economic group hotels; 3) when it was used the added scale, the luxury group hotels superiority prevailed again, not only in management variables but also in achievement in relation to the economic group and; 4) besides, it was evidenced that 46,4% from the total of analyzed variables differed a group from the other. Considering these results, it can be concluded that there is evidence that the luxury hotels predominance offers a better feed back to the investors, demanding a more efficient management. At last, given the hospitality market dynamicity, it is suggested, to the continuity of this study, the deepening in the variable measures research that compound the demand management, operational capacity immediate supply chain and performance, in order to know exactly the hospitality service nuances, in the different categories.